Pneumatosis intestinalis and pneumoperitoneum secondary to Sapovirus colitis - Thomas O. Xu; Daniel E. Levin (Elsevier, 2019)
Pneumatosis intestinalis (PI) with pneumoperitoneum are radiographic findings that may be associated with severe bowel compromise. Asymptomatic patients with benign pneumoperitoneum are well described and can typically be observed. Among symptomatic patients, these findings are more concerning and often mandate operative intervention. The common etiologies of PI with pneumoperitoneum in children can typically be determined by history, physical and imaging findings. Viral enteritis and colitis is an infrequent cause. Sapovirus is in the family Caliciviridae. It is similar to norovirus, a more common pathogen in acute gastroenteritis, but typically presents with less severe symptoms. Here, we describe the presentation of an 11 year old, immune competent boy with severe abdominal pain, PI and pneumoperitoneum. Diagnostic laparoscopy revealed viable bowel without the need for resection or diversion. Stool pathogen panel revealed Sapovirus infection. He made a complete recovery. To our knowledge, this is the first description of PI with pneumoperitoneum caused by Sapovirus infection. Keywords: Pneumoperitoneum, Sapovirus, Pneumatosis intestinalis